Occludin controls HIV transcription in brain pericytes via regulation of SIRT‐1 activation. Issue 3 (24th November 2015) - Castro, Victor; Bertrand, Luc; Luethen, Mareen; Dabrowski, Sebastian; Lombardi, Jorge; Morgan, Laura; Sharova, Natalia; Stevenson, Mario; Blasig, Ingolf E.; Toborek, Michal
Abstract : HIV invades the brain early after infection; however, its interactions with the cells of the blood‐brain barrier (BBB) remain poorly understood. Our goal was to evaluate the role of occludin, one of the tight junction proteins that regulate BBB functions in HIV infection of BBB pericytes. We provide evidence that occludin levels largely control the metabolic responses of human pericytes to HIV. Occludin in BBB pericytes decreased by 10% during the first 48 h after HIV infection, correlating with increased nuclear translocation of the gene repressor C‐terminal‐binding protein (CtBP)‐1 and NFκB‐p65 activation. These changes were associated with decreased expression and activation of the class III histone deacetylase sirtuin (SIRT)‐1. Occludin levels recovered 96 h after infection, restoring SIRT‐1 and reducing HIV transcription to 20% of its highest values. We characterized occludin biochemically as a novel NADH oxidase that controls the expression and activation of SIRT‐1. The inverse correlation between occludin and HIV transcription was then replicated in human primary macrophages and differentiated monocytic U937 cells, in which occludin silencing resulted in 75 and 250% increased viral transcription, respectively. Our work shows that occludin has previously unsuspected metabolic properties and is a target of HIV infection, opening the possibility of designing novel pharmacological approaches to control HIV transcription.—Castro, V., Bertrand, L., Luethen, M., Dabrowski, S., Lombardi, J., Morgan, L., Sharova, N., Stevenson, M., Blasig, I. E., Toborek, M., Occludin controls HIV transcription in brain pericytes via regulation of SIRT‐1 activation. FASEB J. 30, 1234–1246 (2016). www.fasebj.org